(untitled) (Contemporary Journal of Social Science Review, 2025)
Background: University-level sports systems in developing countries depend heavily on governing bodies to provide policy direction, funding, and talent development infrastructure. In Pakistan, the Higher Education Commission (HEC) occupies this central role, yet stakeholder perceptions of its effectiveness remain empirically underexplored. Objective: This study investigated how university athletes and coaches perceive HEC’s contribution to sports education and talent development, examining five key domains: policy and governance, financial and infrastructure support, talent identification, capacity building, and institutional environment. Methods: A quantitative descriptive-comparative design was employed. Using purposive sampling, 200 participants were recruited from public and private universities across six provinces of Pakistan 150 athletes (75%) and 50 coaches (25%). A 25-item structured questionnaire based on a 5-point Likert scale was administered. Data were analyzed through chi-square tests, independent-samples t-tests, and Pearson correlation analyses using SPSS (α = .05). Results: Chi-square analysis revealed statistically significant variability in responses across all 25 items (all p < .001), indicating diverse stakeholder perceptions. An independent-samples t-test demonstrated that coaches (M = 4.10, SD = 0.50) held more positive perceptions than athletes (M = 3.80, SD = 0.60; t[98] = 2.10, p = .038). Pearson correlations confirmed strong positive interdependencies among all five domains (r = .55–.67, all p < .01). Conclusion: HEC is broadly recognized as a constructive force in university sports, but significant gaps persist in policy implementation, resource equity, and regional consistency. Athletes the primary beneficiaries report comparatively lower satisfaction than coaches, pointing to a critical disconnect between policy intent and ground-level experience.